Impact of interhospital transfer on patients undergoing endovascular thrombectomy for acute ischaemic stroke in an Australian setting. Issue 1 (5th April 2020) - Edwards, Leon Stephen; Blair, Christopher; Cordato, Dennis; McDougall, Alan; Manning, Nathan; Cheung, Andrew; Wenderoth, Jason; Cappelen-Smith, Cecilia
Abstract : Objective: To assess the impact of interhospital transfer on the interplay between functional outcome, mortality, reperfusion rates and workflow time metrics in patients undergoing endovascular thrombectomy (EVT) for acute ischaemic stroke due to large vessel occlusion (LVO) in the anterior cerebral circulation. Design, setting and participants: This is an analysis of a prospective database of consecutive patients undergoing EVT for LVO presenting between January 2017 and December 2018 at a single Australian comprehensive stroke centre (CSC). Patients presented directly or were transferred to the CSC from 21 sites across New South Wales and the Australian Capital Territory. Main outcome measures: The main outcome measures were rate of good 90-day functional outcome (modified Rankin Scale 0–2), successful reperfusion (Thrombolysis in Cerebral Infarction scale grade 2b or 3), symptomatic intracerebral haemorrhage (sICH) and 90-day mortality. Key workflow time metric milestones were examined. Results: 154 of 213 (72%) patients were interhospital transfers. There was no significant difference in baseline characteristics including age, National Institutes of Health Stroke Scale score, intravenous thrombolysis administration or procedure time between transferred and direct presenters (all p>0.05). Transferred patients had worse 90-day functional outcome (39.6% vs 61.0%, OR 0.42, 95% CI 0.23 to 0.78), higher mortality (25.3% vs 6.8%, OR 4.66, CI 1.59 to 13.70) and longer stroke onset to treatment (groin puncture) time (298 min vs 205 min, p<0.01). Successful reperfusion rates and sICH were similar between the cohorts (96.8% vs 98.3%, and 7.8% vs 3.4%). Conclusion: Interhospital transfer is associated with longer stroke onset to treatment, worse 90-day functional outcome and higher mortality compared with patients presenting directly to the CSC.